Evaluation of the outcome of interferon therapy in chronic hepatitis B infection - Rahmet ÇAYLAN,; Kemalettin AYDIN,; İftihar KÖKSAL,; Recep ÖKSÜZ,; Uğur KOSTAKOĞLU,; Ümit ÇOBANOĞLU,; Nurucihan ARI,; Sevim AYDIN, (Turkish Journal of Gastroenterology, 2019)
-